ADVISORY AGENCY MEDIATION EFFORTS FOR MARRIAGE PRESERVATION AND DIVORCE PREVENTION AT THE MEDAN DENAI RELIGIOUS AFFAIRS OFFICE - Andini Andini; Muniruddin Muniruddin (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2024)
This research aims to examine the role of BP4 in the KUA of Medan Denai District, the mediation efforts undertaken, as well as the obstacles and opportunities for successful mediation. The qualitative method employed is descriptive research, which seeks to describe symptoms, incidents, or events that are currently occurring. The research was conducted at KUA Medan Denai District. The research topic was selected using a purposive sampling technique, considering specific aspects or criteria. Subjects are individuals who provide information to researchers. Data collection techniques included observation, interviews, and documentation. The research findings indicate that the role of BP4 in KUA Medan Denai District is to resolve family problems in order to achieve a harmonious and loving family life, characterised by sakinah, mawaddah, and warahmah, by reducing prejudice and egoism between partners. Mediation efforts are carried out in specific stages with guidance provided by an instructor. Obstacles in conducting mediation include the absence of one of the parties and difficulty in controlling emotions, while the opportunities for success in BP4 mediation lie in the availability of infrastructure and instructors who possess knowledge and experience.